(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Food security including its economic, technical and social dimensions is considered to be one of the issues that received wide attention, this food security issue is closely related to the agricultural sector, therefore agricultural sector occupies a very important position in the economics of countries, especially developing countries, including Syria. the agricultural sector has achieved a great success in Syria during its ongoing development, but recently many local and international changes has appeared. These changes had a lot of challenges that must be treated with suitable mechanisms . So This research aims to show the reality of plant and animal production in Latakia, and to acknowledge the most important human and natural components ingredients that are available in agricultural sector, this research aims to find out obstacles and problems that agricultural sector suffers from, and to find perfect solutions for them. It also aims to discover the best way to increase Agricultural Productions in latakia. and that contributes to achieving the agricultural development in Syria providing people of Syria , the food security In addition to economic one .especially in this crisis that gripped Syria.